"Functional" Respiratory Muscle Training During Endurance Exercise Causes Modest Hypoxemia but Overall is Well Tolerated. Issue 3 (March 2016) - Granados, Jorge; Gillum, Trevor L.; Castillo, Weston; Christmas, Kevin M.; Kuennen, Matthew R.
Abstract : Abstract: Granados, J, Gillum, TL, Castillo, W, Christmas, KM, and Kuennen, MR. "Functional" respiratory muscle training during endurance exercise causes modest hypoxemia but overall is well tolerated. J Strength Cond Res 30(3): 755–762, 2016—A novel commercial training mask purportedly allows for combined respiratory muscle training and altitude exposure during exercise. We examined the mask's ability to deliver on this claim. Ten men completed three bouts of treadmill exercise at a matched workload (60%V[Combining Dot Above]O2 peak) in a controlled laboratory environment. During exercise, the mask was worn in 2 manufacturer-defined settings (9, 000 ft [9K] and 15, 000 ft [15K]) and a Sham configuration (∼3, 500 ft). Ventilation (VE ), tidal volume (VT ), respiratory rate (RR ), expired oxygen (FE O2 ) and carbon dioxide (FE CO2 ), peripheral oxygen saturation (SP O2 ), heart rate, and RPE were measured each minute during exercise, and subjects completed the Beck Anxiety Inventory (BAI) immediately after. The mask caused a reduction in VE of ∼20L/min in both the 9K and 15K configurations ( p < 0.001). This was due to a reduction in RR of ∼10 b·min −1, but not VT, which was elevated by ∼250 ml ( p < 0.001). FE O2 was reduced and FE CO2 was elevated above Sham in both 9K and 15K ( p < 0.001). V[Combining Dot Above]O2 was not different across conditions ( p = 0.210), but V[Combining Dot Above]CO2 trended lower at 9K ( p = 0.093) and was reduced at 15K ( p = 0.016). VE /V[Combining Dot Above]O2 was 18.3% lower than Sham at 9K and 19.2% lower at 15K. VE /V[Combining Dot Above]CO2 was 16.2% lower than Sham at 9K and 18.8% lower at 15K (all p < 0.001). Heart rate increased with exercise ( p < 0.001) but was not different among conditions ( p = 0.285). SP O2 averaged 94% in Sham, 91% at 9K, and 89% at 15K ( p < 0.001). RPE and BAI were also higher in 9K and 15K ( p < 0.010), but there was no difference among mask conditions. The training mask caused inadequate hyperventilation that led to arterial hypoxemia and psychological discomfort, but the magnitude of these responses were small and they did not vary across mask configurations.